2019
DOI: 10.1111/1462-2920.14631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐term organic and mineral fertilization strategies on rhizosphere microbiota assemblage and performance of lettuce

Abstract: SummaryLong‐term agricultural fertilization strategies gradually change soil properties including the associated microbial communities. Cultivated crops recruit beneficial microbes from the surrounding soil environment via root exudates. In this study, we aimed to investigate the effects of long‐term fertilization strategies across field sites on the rhizosphere prokaryotic (Bacteria and Archaea) community composition and plant performance. We conducted growth chamber experiments with lettuce (Lactuca sativa L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 68 publications
8
73
2
Order By: Relevance
“…The RA of candidate phylum Latescibacteria (WS3) was highest in unfertilized soils (0.98%). In contrast to our results, Latescibacteria sequences showed higher RA in fertilized agricultural soil samples from the Pampas region (4%) in comparison to pristine soil [9,52]. Both phyla have been shown to correlate positively to soil pH [16], thus the high N ratio might have indirectly reduced their RA by decreasing soil pH.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The RA of candidate phylum Latescibacteria (WS3) was highest in unfertilized soils (0.98%). In contrast to our results, Latescibacteria sequences showed higher RA in fertilized agricultural soil samples from the Pampas region (4%) in comparison to pristine soil [9,52]. Both phyla have been shown to correlate positively to soil pH [16], thus the high N ratio might have indirectly reduced their RA by decreasing soil pH.…”
Section: Discussioncontrasting
confidence: 99%
“…Modern approaches, using phylogenetic surveys of bacteria employing universal primers, allow for characterization and comparison of the microbial diversity in different soil environments as well as the comparative analysis of changes in community structure due to management practices [7,8]. Although numerous studies have examined the influence of N fertilizer on the soil microbiome [9][10][11][12], most of these studies compared responses to organic and inorganic fertilizers; only a few studies examined the response of the soil microbiome to increasing N fertilizer rates in an agroecosystem [11,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that, besides the plant influence, long-term agricultural practices affect the assembly of the rhizosphere microbiota ( Chowdhury et al, 2019 ). It has been observed that recruitment of management process–specific taxa is favored by the plant hosts, which also helps in shifting the nutrient cycling in rhizospheric region ( Schmidt et al, 2019 ).…”
Section: Agricultural Management and Status Of Microbial Inoculantsmentioning
confidence: 99%
“…Before planting of the rice variety YD-1, the total soil N and P concentrations were as high as 2.81 mg g -1 and 0.41 mg g -1 , respectively. Generally, the contribution of crop varieties that affect the microbial community, which includes bacteria, is higher in low-fertile soils (Yao et al, 2018;Chowdhury et al, 2019).…”
Section: Connection Of Nutrient and Soil Bacterial Community Structurementioning
confidence: 99%